Dual, Site‐Specific Modification of Antibodies by Using Solid‐Phase Immobilized Microbial Transglutaminase. (29th August 2017) - Spycher, Philipp R.; Amann, Christian A.; Wehrmüller, Jöri E.; Hurwitz, David R.; Kreis, Olivier; Messmer, Daniel; Ritler, Andreas; Küchler, Andreas; Blanc, Alain; Béhé, Martin; Walde, Peter; Schibli, Roger
Abstract: Microbial transglutaminase (MTG) was stably solid‐phase immobilized on glass microbeads by using a second‐generation dendronized polymer. Immobilized MTG enabled the efficient generation of site‐specifically conjugated proteins, including antibody fragments, as well as whole antibodies through distinct glutamines and, unprecedentedly, also through lysines with various bifunctional substrates with defined stoichiometries. With this method, we generated dual, site‐specifically modified antibodies comprising a fluorescent probe and a metal chelator for radiolabeling—a strategy anticipated to design antibodies for imaging and simultaneous therapy. Furthermore, we provide evidence that immobilized MTG features higher siteselectivity than soluble MTG. Abstract : Double take : Solid‐phase immobilized microbial transglutaminase (MTG) enables the site‐specific modification of glutamine and/or lysine residues of various proteins with probes suitable for bioorthogonal click reactions. Site‐specific, dual modification of antibodies is demonstrated with chemical entities suitable for dual‐imaging applications without affecting antibody–antigen binding.